Bis(benzenethiolato)(2,2′-biquinoline)zinc(II) - Thomas Blake Monroe (Acta Crystallographica Section E, 2009)
The title compound, [Zn(C6H5S)2(C18H12N2)], was prepared as a model for future complexes that will be incorporated into light-harvesting arrays. The ZnII atom lies on a twofold rotation axis and the ligands are arranged tetrahedrally around this atom. The benzenethiolate ligand and the biquinoline ligand are nearly perpendicular to one another, making a dihedral angle of 84.09 (5)°. The biquinoline ligand is nearly planar, with a maximum deviation of 0.055 (3) Å from the mean plane of the ring system. In the crystal, the molecules pack in a manner such that the biquinoline ligands are parallel to one another, with a π–π interaction [interplanar distance = 3.38 (1) Å] with the neighboring biquinoline ligand.